Respuesta :

Answer:

A. y + 1 = -3(x - 4)

Step-by-step explanation:

If the equations are perpendicular, then that means they have the same slope, just with the opposite sign. In this case, the given equation's slope is 3, which means that the other equation's slope is -3. Now that we know the slope and one point, we can write the equation in point-slope form:

y - y1 = m(x - x1)

y - (-1) = -3(x - 4)

y + 1 = -3(x - 4)

The equation in point-slope form is answer choice A. y + 1 = -3(x - 4).

Hope this helps :)

ACCESS MORE